Zsazsa Zaturnnah sa kalakhang Maynila #1ng tatlong bahagi - Vergara, Carlo (Visprint, 2011)
Zsazsa Zaturnnah sa kalakhang Maynila is the sequel to the award-winning graphic novel. This is the first of three parts.